The Influence of Disruptive Innovation, Organisational Capabilities and People on Organisational Performance among Manufacturing based Companies in Malaysia - Koay, Hooi Gee; Muthuveloo, Rajendran (Journal of Entrepreneurship, Business and Economics, 2021)
Organisational performance has become the main issue as organisations are struggling for business sustainability. Organisations have not achieved the expected organisational performance in the dynamic environment. This research aims to examine the influence of disruptive innovation, organisational capabilities, and people on organisational performance. A quantitative study was designed, and one hundred and twenty-one (121) data among organisations involved in the manufacturing of electrical and electronics (E&E) products in Malaysia were gathered through a structured questionnaire using stratified sampling techniques. Data gathered were analysed with SPSS software version 24 and Smart Partial Least Squares-Structural Equation Modeling (PLS-SEM) version 3.2.7. The result demonstrated that disruptive innovation, organisational capabilities, and people significantly influence organisational performance. From the academic aspect, the conceptual framework articulated based on the research gap, the I-TOP Strategic Agility model, and dynamic capabilities theory provides more insights into optimising organisational performance. In addition, this study measured organisational performance from the perspective of happiness that comprises of employee happiness, customer happiness, and shareholder happiness. Practitioners could utilise this study's findings to formulate a more effective strategy to optimise their organisational performance that is critical for business sustainability. Research paper Keywords: Organisational Performance; Disruptive Innovation; Organisational Capabilities; People; I-TOP Strategic Agility Model Reference to this paper should be made as follows: Koay, H. G., & Muthuveloo, R. (2021). The Influence of Disruptive Innovation, Organisational Capabilities and People on Organisational Performance among Manufacturing based Companies in Malaysia. Journal of Entrepreneurship, Business and Economics , 9 (1), 163–201.